Rapid, facile synthesis of InSb twinning superlattice nanowires with a high-frequency photoconductivity response. Issue 32 (28th May 2021) - Qian, Yinyin; Xu, Kaijia; Cheng, Lanjun; Li, Cunxin; Wang, Xingchen
Abstract : We present a self-seeded solution–liquid–solid (SLS) synthesis route for InSb nanowires (NWs) using commercially available precursors at a relatively low temperature of about 175 °C, which takes only 1 min upon the injection of reductant. Abstract : We present a self-seeded (with indium droplets) solution–liquid–solid (SLS) synthesis route for InSb nanowires (NWs) using commercially available precursors at a relatively low temperature of about 175 °C, which takes only 1 min upon the injection of reductant. Structural characterization reveals that the InSb nanowires are high quality and have twinning superlattice structures with periodically spaced twin planes along the growth direction of 〈111〉. Notably, we have measured an ultrafast conductivity lifetime in the NWs of just 9.1 ps utilizing time-resolved optical pump-terahertz probe (OPTP) spectroscopy, which may facilitate the development of high-frequency nanoscale integrated optoelectronic systems related to twinning superlattice structures.